S n = i = 0 ∑ n − 1 j = 0 ∑ i − 1 k = 0 ∑ j − 1 ( i + j + k ) S 3 1 + S 4 1 + S 5 1 + ⋯ = A − B 2 π 2
A and B are positive integers. Find A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
S n = i = 0 ∑ n − 1 j = 0 ∑ i − 1 k = 0 ∑ j − 1 ( i + j + k )
Since ∑ i = 0 n i = 2 n ( n + 1 ) :
S n = i = 0 ∑ n − 1 j = 0 ∑ i − 1 i j + j 2 + 2 ( j − 1 ) j
S n = i = 0 ∑ n − 1 j = 0 ∑ i − 1 i j + 2 3 j 2 − 2 j
Since ∑ i = 0 n i 2 = 6 n ( n + 1 ) ( 2 n + 1 ) :
S n = i = 0 ∑ n − 1 i [ 2 ( i − 1 ) i ] + 2 3 [ 6 ( i − 1 ) i ( 2 i − 1 ) ] − 4 ( i − 1 ) i
S n = i = 0 ∑ n − 1 i 3 − 2 3 i 2 + 2 i
Since ∑ i = 0 n i 3 = [ 2 ( n + 1 ) n ] 2 :
S n = 4 ( n − 1 ) 2 n 2 − ( n − 1 ) n ( 2 n − 1 ) + ( n − 1 ) n
S n = 4 ( n − 1 ) n [ ( n − 1 ) n − ( 2 n − 1 ) + 1 ]
S n = 4 ( n − 1 ) n [ ( n 2 − 3 n + 2 ) ]
S n = 4 n ( n − 2 ) ( n − 1 ) 2
We're looking for:
S = n = 3 ∑ ∞ S n 1
S = 4 n = 3 ∑ ∞ n ( n − 2 ) ( n − 1 ) 2 1
By partial fractions:
S = 4 ⎣ ⎡ n = 3 ∑ ∞ 2 1 ( n − 2 1 − n 1 ) − n = 3 ∑ ∞ ( n − 1 ) 2 1 ⎦ ⎤
The first sum will telescope, and only the first two terms of the first fraction will remain. On the second sum, we make m = n − 1 :
S = 4 ⎣ ⎡ 2 1 ( 1 + 2 1 ) − m = 2 ∑ ∞ m 2 1 ⎦ ⎤
S = 4 ⎣ ⎡ 4 3 − ⎝ ⎛ m = 1 ∑ ∞ m 2 1 − 1 ⎠ ⎞ ⎦ ⎤
S = 4 [ 4 7 − 6 π 2 ]
S = 7 − 3 2 π 2
Thus:
A = 7 , B = 3 , A + B = 1 0